Analisis Yuridis Penegakan Hukum dan Pencegahan Tindakan Pengerusakan dalam Lingkup Pariwisata Berdasarkan dari Asas Good Governance - Lexandru Josep Kusumo; Demson Tiopan (UNES Law Review, 2023)
Destructive actions can be categorized as vandalism. This destructive action is common in tourism areas. Tourism is an important sector of national economic development. The tourism sector faces challenges in the form of acts of vandalism on public facilities that result in losses for the tourism sector and indicate the existence of social diseases in Indonesia. This problem is important to be addressed through law enforcement and prevention efforts in accordance with the principles of good governance because the lack of government supervision in terms of order has caused problems in the form of a social disease called vandalism which is rampant in tourism sites. Therefore, it is necessary to conduct research to examine legal prevention and efforts to prevent this act of vandalism in terms of the principles of good governance. The method used for this research is the normative juridical method in which the research focuses on positive legal norms written in and the Criminal Code (KUHP) relating to sanctions. The purpose of this research is to find out whether law enforcement and prevention of acts of destruction in the tourism environment are in accordance with the principles of good governance. The form of sanctions against the perpetrator is regulated in the Criminal Code. One of the efforts that can be made to reduce this act of destruction in accordance with the principles of good governance is to facilitate these street artists to help the government beautify tourism in Indonesia.